Modeling non-axisymmetry in the DIII-D small angle slot divertor using EMC3-EIRENE - J.D. Lore; P.C. Stangeby; H.Y. Guo; B. Covele; A. Moser; H. Frerichs (Nuclear Materials and Energy, 2018)
The 3D edge transport code EMC3-EIRENE is used to evaluate the effects of non-axisymmetric misalignment of the small angle slot (SAS) divertor on DIII-D. The SAS is a slot divertor with a close-fitting baffle designed to control neutral recycling to yield a wide region of low electron temperature across the divertor near the strike point and to achieve mitigated heat flux to the divertor at a lower upstream plasma density as compared to a more open geometry. The measured misalignment is simulated as an n = 1 sinusoidal offset in major radius of magnitude 5.1 mm, resulting in toroidally varying divertor conditions where local regions of high and low fluxes and a changing level of detachment can be supported. The trends can be understood in terms of the local incident angle of the magnetic field, the volume of the private flux plasma in the slot, and the energy losses along the field lines in the slot. The misaligned SAS is globally more attached and has a lower plasma density and particle flux than an axisymmetric solution. Computational grids limited to the radial extent of the slot result in artificially detached solutions unless the cross-field transport coefficients are reduced such that the heat flux width is smaller than the grid width.